2011
DOI: 10.1155/2011/230597
|View full text |Cite
|
Sign up to set email alerts
|

Association of Heavy Rainfall on Genotypic Diversity inV. choleraeIsolates from an Outbreak in India

Abstract: The outbreak of waterborne disease cholera has been associated with rainfall and flooding events by contamination of potable water with environmental Vibrio cholerae. The continuation of the epidemic in a region, however, is often due to secondary transmission of the initial outbreak strain through human waste. This paper reports, on the contrary, a rapid shift of genotype from one V. cholerae strain to another one in an epidemic region. V. cholerae isolated from patients during 2005 cholera epidemic in Chenna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…It has been hypothesised that the serological switching and genetic diversity of strains between pandemics and epidemics may be influenced by climate variations, with global warming making the environment favourable for cholera outbreaks by switching of virulence factors. This hypothesis is supported by studies of V. cholerae outbreaks in India [9], Bangladesh [10] and China [11], as well as a literature review of the influence of environmental factors on V. cholerae presence [12]. Furthermore, experimental studies have demonstrated variation with changes in environmental conditions in expression of ChiA2 and TfoX, key regulators of V. cholerae horizontal gene transfer [13].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…It has been hypothesised that the serological switching and genetic diversity of strains between pandemics and epidemics may be influenced by climate variations, with global warming making the environment favourable for cholera outbreaks by switching of virulence factors. This hypothesis is supported by studies of V. cholerae outbreaks in India [9], Bangladesh [10] and China [11], as well as a literature review of the influence of environmental factors on V. cholerae presence [12]. Furthermore, experimental studies have demonstrated variation with changes in environmental conditions in expression of ChiA2 and TfoX, key regulators of V. cholerae horizontal gene transfer [13].…”
Section: Introductionmentioning
confidence: 78%
“…They have identified heavy rainfall as the plausible cause of genotype switching between O1 and O139 type strain. The duration between two peaks and switching was only 2 weeks [ 9 ]. Koelle et al also showed in Bangladesh through a phenotypical modelling that shifting in V. cholerae serotype is driven chiefly by environmental variations rather than by human-borne dissemination [ 10 ].…”
Section: Virulence Factor and Transductionmentioning
confidence: 99%
“…The ERIC-PCR has widely been applied to analyze bacterial genotyping in epidemiology (Ranjbar et al 2010). It has also been used for the analysis of clonal diversity and genotypic variability of V. cholera strains from aquatic environment (Goel and Jiang 2011; Rivera et al 1995). Previous studies reported that ERIC-PCR yielded one to eight DNA amplicons in the size ranging from 100 to 4000 bp (Rivera et al 1995; Colombo et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Genotypic diversity among V. cholerae has been attributed to several reasons. Natural calamities such as heavy rainfall may support the spread of mixed genotypes in a population (Goel and Jiang 2011). In 2004, the substituted Inaba strains were identified as ribotype R-IV and H-1 pulsotype that is very close to the pattern exhibited by Ogawa strains isolated during the same period in Kolkata ).…”
Section: Molecular Epidemiology Of Choleramentioning
confidence: 62%